Contextualizing Luqman's Wisdom in Qur'anic Character Education within the Indonesian Curriculum - Alhamuddin, Alhamuddin; Murniati, Andi; M. Syukri Ismail; Imam Pamungkas (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study explores how character values from Surah Luqman verse 13-19 can be integrated into Indonesia's character education curriculum. The main issue addressed is the gap between the ethical-religious ideals emphasized in national policies, such as the Pancasila Student Profile and the Guidelines for Strengthening Character Education, and their limited implementation in schools, where academic performance often prioritizes moral development. Using a qualitative library research approach, the study analyzed classical and contemporary Qur'anic interpretations, scholarly works, and official educational documents. Through thematic analysis of Luqman's advice, key values such as monotheism (tauhid), respect for parents, spiritual awareness, patience, humility, social responsibility, and ethical communication were identified and aligned with Indonesia's character education framework. These values were compared with curriculum indicators and policy guidelines, showing their relevance for teaching practices and school culture. The findings highlight that these values are consistent with Islamic educational traditions and modern character education theory. The study recommends that policymakers and educators adopt a more holistic approach, integrating Qur'anic values into curriculum content, teaching strategies, and school environments, to support students' moral and spiritual development. This approach offers a practical model for making character education in Indonesia more meaningful and transformative.